Nail-Patella Syndrome Associated with Short Stature: A Case Series - Samir Haddad; Leila Ghedira-Besbes; Chahra Bouafsoun; Sabeur Hammami; Slaheddine Chouchene; Chebil Ben Meriem; Mohamed-néji Guediche (Case Reports in Medicine)
Introduction. Nail-patella syndrome (NPS) is a rare genetic disorder that is characterized by a pleiotropic malformation affecting the nail, the skeleton, and occasionally the central nervous system and the kidneys. Case Presentation. We report two paediatric cases, which are of two sisters, who aged, respectively, two and five years. They are admitted to explore short stature. The initial clinical examination and radiologic findings confirmed the diagnosis of Nail-patella syndrome. Conclusion. Skeletal, ophthalmologic, and renal involvements were mostly associated with NPS. The association with short stature was exceptional.